The Role of Stakeholders’ Expectations and Organisational Culture in Sustainable Port Operations: The Case of Saudi Arabia - Alharbi, Talal (Curtin University, 2023)
This study investigates how stakeholder expectations (SHE), efficient operations (EO), and organisational culture (OC) affect port sustainability practices (PSP) in Saudi Arabia. Using mixed-methods research, 12 interviews and a survey questionnaire completed by 239 participants, analysed through partial least squares–based structural equation modeling. The study finds that SHE significantly influences PSP and that OC moderates this relationship. The study contributes to the literature and provides guidelines for port investors and authorities on achieving PSPs.